Traditional Kalakatar dessert in Perak / Noorliza Zainol … [et al.] - Zainol, Noorliza; Razali, Mohamad Azli; Syed Hamzah, Syarifah Atifah; Abdullah, Siti Khadijah (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
Perak, a state in northern Malaysia known for its lush landscapes, historic sites, and cultural richness, is home to a lesser-known culinary gem: Kalakatar. This traditional delicacy offers a unique glimpse into Perak's vibrant food culture and is a testament to the state's rich culinary traditions. Despite its relatively low profile compared to more famous Malaysian dishes, Kalakatar represents a significant part of Perak's heritage.